Evaluation of Cholesterol Lowering Efficacy and Antibacterial Potential of Probiotics: An In vitro Study - Aman, Ayisha; Shamim, Tooba; Siddiqui, Ayesha; Naheed, Suad (Anti-Infective Agents, 2021)
Background and Objectives: Probiotics are nonpathogenic and beneficial viable microorganisms that exhibit potential health welfare for human beings. Probiotics are found in various food products. They also occur as natural microflora in the intestine of mammals. Main goal of this study was to isolate probiotics conferring antibacterial activity and cholesterol lowering ability from different fruits. Materials and Methods: Present research reveals the usefulness of probiotics, in which twenty one bacterial cultures were isolated from different fruit samples including figs, coconut water and grapes. These strains were explored for their antibacterial and cholesterol reduction ability by conducting in vitro experiments. Results and Discussion: Among twenty one isolates, nine probiotic cultures FgC2, FgC7, FgC14, G2C5, G1C, GrC18 and StCW showed maximum antibacterial activity against different human clinical pathogens. This suggests that these microbes produce inhibitory metabolites which are extracellular and diffusible. For cholesterol assimilation assay, six strains FgC2, FgC7, FgC12, FgC13, GrC7 and GrC18 presented remarkable cholesterol lowering efficacy (up to 98%) when grown in the presence of bile salts. Only potential probiotic cultures were identified and characterized as lactic acid bacteria (LAB), on the basis of Bergey’s Manual of Determinative Bacteriology. Conclusion: Thus, this study is helpful to exploit the bioactive and therapeutic potential of beneficial microorganisms so that they can be utilized in the generation of functional food and other health promoting products.
Keywords: lactic acid bacteria